The thought of Ernesto Cardenal and Martín Baró: social revolution and political commitment of two liberation theologians - Barrientos Valverde, Jorge (2022)
In the turbulent context of the Cold War, there existed within the Catholic Church, at least since the 1960s, serious divisions between religious sectors. Between conservative groups and more progressive movements there were serious political tensions. Within this last movement a movement called Liberation Theology developed, in response to the most elitist, racist and class sectors of hegemonic Catholicism. Ernesto Cardenal and Martín Baró were followers and representatives of this movement. This article develops a modest study of some of the main ideas of these two social activists and representatives of the Catholic Church, to better understand the world of their subjectivities, their analyzes of Central American society and the proposals they raised to solve the most common problems. serious issues that we faced during the eighties from the application of a comparative analysis.